Bash Cookbook Leverage Bash scripting to automate daily tasks and improve productivity - Brash, Ron (Packt Publishing Limited, 2018)
bCreate simple to advanced shell scripts and enhance your system functionality with effective recipes/b h4Key Features/h4 ulliAutomate tedious and repetitive tasks/li liCreate several novel applications ranging from a simple IRC logger to a Web Scraper/li liManage your system efficiently by becoming a seasoned Bash user/li /ul h4Book Description/h4 In Linux, one of the most commonly used and most powerful tools is the Bash shell. With its collection of engaging recipes, Bash Cookbook takes you through a series of exercises designed to teach you how to effectively use the Bash shell in order to create and execute your own scripts. The book starts by introducing you to the basics of using the Bash shell, also teaching you the fundamentals of generating any input from a command. With the help of a number of exercises, you will get to grips with the automation of daily tasks for sysadmins and power users.